2019
DOI: 10.1101/546630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CONSENT: Scalable long read self-correction and assembly polishing with multiple sequence alignment

Abstract: Motivation: Third-generation sequencing technologies Pacific Biosciences and Oxford Nanopore allow the sequencing of long reads of tens of kbp, that are expected to solve various problems, such as contig and haplotype assembly, scaffolding, and structural variant calling. However, they also display high error rates that can reach 10 to 30%, for basic ONT and non-CCS PacBio reads. As a result, error correction is often the first step of projects dealing with long reads. As first long reads sequencing experiment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…The raw reads were assembled into 47 scaffolds (22.9 Mbp) with one gap using MaSuRCA 3.3.2 49 . The nanopore reads were corrected using CONSENT v1.1.2 50 . The paired-end reads were corrected using Trimmomatic version 0.36 51 .…”
Section: Methods For Genome and Transcriptome Analysismentioning
confidence: 99%
“…The raw reads were assembled into 47 scaffolds (22.9 Mbp) with one gap using MaSuRCA 3.3.2 49 . The nanopore reads were corrected using CONSENT v1.1.2 50 . The paired-end reads were corrected using Trimmomatic version 0.36 51 .…”
Section: Methods For Genome and Transcriptome Analysismentioning
confidence: 99%
“…As for hybrid correction, other methods, such as CONSENT [54], combine these two approaches, in order to counterbalance their advantages and their drawbacks. We describe each approach more into details, and list the related tools, in the following subsections.…”
Section: Self-correctionmentioning
confidence: 99%
“…As for hybrid correction, some methods also rely on combinations of the two previously described strategies. For instance, CONSENT [54] relies on both multiple sequence alignment and de Bruijn graphs, which it combines into a two-step error correction process.…”
Section: Combination Of Strategiesmentioning
confidence: 99%
“…As (Lima et al 2019) found that applying genomic error correctors to ONT transcriptome data had undesirable downstream effects, we only evaluated the genomic error corrector CONSENT (Morisse et al 2019) that was not evaluated in (Lima et al 2019) as well as canu (Koren et al 2017) and concluded similarly to (Lima et al 2019) that they are not suitable for long transcriptomic reads (see Supplementary note C). We instead focused on comparing our tool to a recent long transcriptomic read error correcting tool RATTLE (de la Rubia et al, 2020 ) .…”
Section: Comparison Against Other Toolsmentioning
confidence: 99%